2008
DOI: 10.1001/archinternmed.2007.32
|View full text |Cite
|
Sign up to set email alerts
|

Increased Bleeding Risk With Concurrent Use of Selective Serotonin Reuptake Inhibitors and Coumarins

Abstract: In users of coumarins, SSRI usage was associated with increased risk of hospitalization because of nongastrointestinal bleeding but not because of gastrointestinal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 23 publications
4
83
3
2
Order By: Relevance
“…This mechanism has not been clearly explained, but recent epidemiological data have demonstrated that SSRIs could significantly increase the risk of gastro-intestinal bleeding [46,47]. According to some studies, the use of SSRIs among the population treated with coumarins seems to place patients at an increased risk of bleeding [15,48,49]. A warning should be added to make the physician aware of this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism has not been clearly explained, but recent epidemiological data have demonstrated that SSRIs could significantly increase the risk of gastro-intestinal bleeding [46,47]. According to some studies, the use of SSRIs among the population treated with coumarins seems to place patients at an increased risk of bleeding [15,48,49]. A warning should be added to make the physician aware of this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…[112][113][114] Similarly, some studies suggest that selective serotonin reuptake inhibitors, tramadol, acetaminophen, coenzyme Q, and ginger may increase the risk of bleeding, but these also require confi rmation. 103,105,106,116,117 Recommendations 3.8. For patients taking VKAs, we suggest avoiding concomitant treatment with NSAIDs, including COX-2-selective NSAIDs, and certain antibiotics (Grade 2C) .…”
Section: Vka Drug Interactions To Avoidmentioning
confidence: 99%
“…In a large community‐based observational AF cohort, we previously found an adjusted relative risk for major hemorrhage of 1.41 (95% CI, 1.04–1.92) with the addition of SSRIs to warfarin 26. Several studies using large national databases have reported that concomitant use of SSRIs with vitamin K antagonists increased the risk of hospitalized bleeding events by roughly 30% to 70%, and a recent nested case‐control study from the United Kingdom Clinical Practice Datalink found an odds ratio of 1.73 (95% CI, 0.89–3.39) for intracranial hemorrhage in patients taking warfarin when SSRIs were added 15, 24, 25, 27. Although the CIs overlapped to varying degrees, our point estimate hazard ratio, SSRI versus no‐SSRI, of 1.16 was smaller than those previously reported and close to the null value of 1.0.…”
Section: Discussionmentioning
confidence: 99%
“…Further, SSRIs inhibit the cytochrome P450 metabolic pathway, potentially increasing warfarin's effect 21, 22, 23. Several studies have reported that the combination of warfarin and SSRIs leads to an increased risk of major hemorrhage 24, 25, 26, 27, 28. No study has yet examined the possible drug‐drug interaction between SSRIs and non–vitamin K antagonist oral anticoagulants.…”
Section: Introductionmentioning
confidence: 99%